1979
DOI: 10.1111/j.1365-2133.1979.tb15293.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of H1 and H2 histamine antagonists on symptomatic dermographism

Abstract: In ten patients suffering from symptomatic dermographism the combined administration of chlorpheniramine + cimetidine produced a greater reduction in the weal and flare response provoked by a standardized scratch than the administration of chlorpheniramine alone. There was a statistically significant improvement in the overall assessment of the patient's skin condition with the combined administration of chlorpheniramine + cimetidine. Chlorpheniramine given alone produced no significant benefit whilst cimetidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 3 publications
1
10
1
Order By: Relevance
“…Matthews et al (1973) showed in a double-blind trial involving thirty-three patients with symptomatic dermographism that Equipose (hydroxyzine), 75 mg daily, decreased wealing to a significantly greater extent than did chlorpheniramine, 12 mg daily, and was preferred by the patients. Two further double-blind trials involving respectively ten and nineteen patients demonstrated that a combination of chlorpheniramine (16 mg daily) and cimetidine (1600 mg daily) produced a significantly greater reduction in wealing than did either chlorpheniramine or cimetidine alone (Matthews et al, 1979;Kaur, Greaves & Eftekhari, 1981). The present study has confirmed and extended these previous observations.…”
Section: Aetiology and Laboratory Investigationssupporting
confidence: 86%
See 1 more Smart Citation
“…Matthews et al (1973) showed in a double-blind trial involving thirty-three patients with symptomatic dermographism that Equipose (hydroxyzine), 75 mg daily, decreased wealing to a significantly greater extent than did chlorpheniramine, 12 mg daily, and was preferred by the patients. Two further double-blind trials involving respectively ten and nineteen patients demonstrated that a combination of chlorpheniramine (16 mg daily) and cimetidine (1600 mg daily) produced a significantly greater reduction in wealing than did either chlorpheniramine or cimetidine alone (Matthews et al, 1979;Kaur, Greaves & Eftekhari, 1981). The present study has confirmed and extended these previous observations.…”
Section: Aetiology and Laboratory Investigationssupporting
confidence: 86%
“…Champion et al (1969) found no peak age of onset, whereas Kirby et al (1971) reported that 41% of cases were between the ages of fifteen and twenty-five. Champion et al (1969) reported a duration of at least 7 years in 90% of forty-seven cases, and Matthews et al (1979) noted a mean duration of 5 years (range: 4 months to 22 years) in a series often patients. Kirby et al (1971), however, reported that follow-up of twenty cases showed a decrease in dermographometer-induced weal size over a 2 to 12 month period, 25% of patients being asymptomatic when they were off treatment after one year.…”
Section: Natural Historymentioning
confidence: 98%
“…The mean duration in two series was 5 years [Matthews et al, 1979;Breathnach et al, 19831 and was at least 7 years in another series [Champion et al, 19691. Kirby et a1 [I9711 reported 20 cases in which a decrease in whealing was observed over a period of 2-12 months; 25% of patients became asymptomatic after 1 year.…”
Section: The Mechanically Induced Urtlcarlas Dermographismmentioning
confidence: 97%
“…The dermographism is best controlled by H1-anti-histamines, H 2 -receptor antagonists having a small additional effect (MATTHEWS et al 1979;COOK and SHUSTER 1983). The increased release of histamine on mechanical challenge (GREAVES and S0NDERGAARD 1970a) appears to result from mast cell fragility, though some neurogenic mechanism has not been excluded.…”
Section: G Clinical Conditions Associated With Histamine In Skinmentioning
confidence: 99%